Depoliticization of the Uleebalangs Descendants Due to a History of Past Violent Conflicts - Teuku Kemal Fasya; Rizki Yunanda; Dedi Fariadi (FISIP Universitas Malikussaleh, 2023)
The study deals with the tragedy of violence that victimized the Uleebalangs and their descendants. This event happened at the beginning of Indonesia's independence (late 1945 to 1946) and continued when the DI/TII movement emerged between 1953 and 1962, known as Prang Cumbok ( war of Cumbok ). This research was conducted on the descendants of Uleebalangs who know the stories of violence experienced by their families in the city of Lhokseumawe, in the province of Aceh. This fact is interesting to examine because it is valuable in reconstructing the historical truth of the massacre of the Uleebalangs by the PUSA group. The study was conducted using a qualitative ethnographic approach. Data collection was carried out through live in, observation, in-depth interviews, focus group discussions (FGD) and document reviews. The data analysis process was carried out interactively through six different steps; data collection, data verification, data models, data coding, thematic data networks, meaning and conclusion. The results of this study indicate that the tragedy of Prang Cumbok is one of the dark stories that happened in Aceh at the beginning of Indonesia's independence. This tragedy has been forgiven by most of the families of the victims, but it has not been forgotten. Therefore, a fair historical reconstruction of the Cumbok tragedy is central to sustainable development planning in Aceh.Studi Penelitian ini membahas tentang tragedy kekerasan yang menjadikan Uleebalang dan keluarganya sebagai korban. Peristiwa itu terjadi pada awal kemerdekaan (akhir 1945 hingga 1946) dan berlanjut ketika Gerakan DI/TII muncul (1953-1962), yang terkenal dengan sebutan perang Cumbok. Beberapa studi kasus kekerasan pernah dialami oleh beberapa keluarga keturunan Ulee Balang di Kota Lhokseumawe Provinsi Aceh. Kenyataan ini menarik dikaji untuk merekonstruksi kebenaran sejarah pembantaian Ulee Balang oleh kelompok PUSA. Studi dilakukan dengan pendekatan kualitatif etnografis. Pengumpulan data dilakukan melalui Live in, observasi, wawancara mendalam, diskusi kelompok terfokus (FGD) dan studi dokumen. Proses analisis data dilakukan secara interaktif melalui tahapan; pengumpulan data, verifikasi data, pola-pola data, pengodean data, jaringan tematik data, makna dan penarikan kesimpulan. Hasil penelitian ini menunjukkan bahwa, Tragedi perang Cumbok merupakan salah satu sejarah kelam yang terjadi di Aceh pada awal kemerdekaan Indonesia. Tragedi tersebut telah dimaafkan oleh sebagian besar keluarga korban, namun tidak dilupakan. Perlu ada rekonstruksi sejarah tragedi Cumbok yang adil untuk kepentingan perencanaan pembangunan berkelanjutan di Aceh.